Gone fishing : a novel in verse - Wissinger, Tamera Will.; Cordell, Matthew (Boston : Houghton Mifflin, 2013)
In this novel told through poems, nine-year-old Sam loves fishing with his dad, so when his pesky little sister horns in on their fishing trip, he is none too pleased. Includes primer on rhyme, poetry techniques, rhythm, stanzas, and poetic forms.
Publisher's Weekly, December 2012
Includes bibliographical references (p. 120).
2.0
K-3
Keywords: Novels in verse; Fishing -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Novels in verse; Fishing -- Fiction; Brothers and sisters -- Fiction; Fishing -- Fiction; Siblings -- Fiction